Papers of Frank Gare - Gare, Frank Ellis, 1918-2003. (1937)
The collection comprises reports, correspondence, official papers, cuttings, photographs, and personal documents.
Manuscript reference no.: MS Acc05.064.
National Library of Australia Oral History collection ORAL TRC 5000/14.
Public servant. Gare served as Western Australia's last Commissioner for Native Welfare for 17 years, 1962-1979. This position meant personal responsibility for the welfare of every Aboriginal man, woman and child in the state. After Gare began work for the WA Department of Native Welfare he accepted a transfer to Geraldton, where he was district officer for the Murchison region. Gare's thinking departed from that of earlier Commissioners and he regarded education, housing and health care as essential factors in the successful assimilation of Aborigines with non-Aborigines. Later Gare was involved in the establishment of the Aboriginal Affairs Planning Authority and the creation of the Aboriginal Lands Trust. He served under the David Brand, John Tonkin and Charles Court governments. In 1941 he married author and artist Nene Gare (birth name: Doris Violet May Wadham).
Keywords: Gare, Frank Ellis, -- 1918-2003 -- Archives; Western Australia. -- Dept. of Native Welfare -- Officials and employees -- Archives; Aboriginal Australians -- Western Australia; Aboriginal Australians -- Government policy -- Western Australia; Public servants